DEVELOPMENT OF METHODOLOGICAL APPROACHES TO INCREASE THE EFFICIENCY OF USING COMPETITIVE INTELLIGENCE SYSTEMS IN ENTERPRISES (Marketing Journal, 2025)
The article explores the potential of advanced technologies for developing competitive intelligence systems in enterprises. The advantages of Attention -LSTM and transfer learning models in predicting customer behavior and forecasting demand for new product s are highlighted. It is shown that machine learning technologies and the FBS -SE methodology play a key role in increasing production efficiency and accelerating decision -making. Digital transformation and green innovations are found 305 to have a positive impact on sustainable development and competitiveness. The research results provide practical recommendations for enhancing the effectiveness of competitive intelligence systems.
Keywords: competitive intelligence; artificial intelligence; machine learning; transfer learning; Attention -LSTM; digital transformation; FBS -SE methodology